The Friends of the Power: The Problems of Friendship in Don Juan Manuel's Thought (14th c.) - Asiss González, Federico Javier (2021)
Friendship is one of the ways to bond with each other and, therefore, a political bond. In the Middle Ages, it was a key element of a political system based on personal relationships. Classical authors, such as Aristotle, had defined it in terms of equality and reciprocity. But, both notions were problematic for medieval thought, sustained in hierarchical links. Among them, Don Juan Manuel stands out, for whom his lineage placed him in such a high social position that he could only have equal treatment with the king. Consequently, this article analyzes, from a political perspective, the forms of friendship created by don Juan Manuel to understand how it is articulated with his theory about a stately government of the kingdom.